X-ray technician examining X-ray. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows technician in x-ray laboratory at Pomona, California Assembly Center.